La sexualité à l'épreuve de la médicalisation : le Viagra - Bajos, Nathalie; Bozon, Michel (Actes de la recherche en sciences sociales, 1999)
Les AA. analysent l'impact du Viagra sur l'evolution des comportements sexuels. Ils distinguent les dysfonctionnements sexuels d'origine organiques et les troubles de l'activite sexuelle lies a des facteurs psychologiques comme le stress. Ils soulignent que le Viagra apparait comme un remede a la defaillance sexuelle. Ils s'efforcent d'evaluer l'impact de la mise sur le marche de ce medicament. Ils mettent en garde contre le risque de renforcement de la norme «erectocentrique», contre le risque d'appauvrissement concomitant du jeu erotique et contre le risque de dependance vis-a-vis du Viagra.
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexualité; inégalités; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Culture, society and sexuality: a reader - Parker, Richard G.; Aggleton, Peter (Social aspects of AIDS, 1999)
Since the beginnings of time, people have been interested in sex - the form it takes, the pleasure it can give, the circumstances in which it occurs, and what it means - both for the individuals concerned and to society more generally. Often seen as a synonym for love, sometimes as an expression of power, and infrequently as a means of exploitation and abuse, sex is a complex and multi-faceted aspect of human behaviour that has been written about by numerous writers and theorists worldwide. This book offers an introduction to the central debates in sexuality research. Among the issues examined are the social and cultural dimensions of sex, human sexuality and sex research. It will be of use to students of sociology, cultural studies, and health and behavioural studies.
Keywords: LGBTQIA2+; VIH; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques

L’individualité féminine à l’épreuve des technologies de reproduction - Van der Ploeg (Cahiers du Genre, 1999)
Cet article décrit l’émergence de deux nouveaux types de patients, le couple et le fœtus, dans certaines techniques reproductives telles la fécondation in vitro et la chirurgie fœtale. Il montre comment l’émergence de ces patients, comme des entités traitables, est liée au développement de ces technologies. Ces pratiques médicales effacent en partie les distinctions entre le naturel et le technique, entre un individu et un autre, et sont accompagnées de dispositifs discursifs spécifiques qui rendent acceptable, voire même naturel ou inévitable le fait de traiter les problèmes de l’enfant ou de l’homme au moyen d’interventions sur le corps de la femme. Cet article est consacré à l’analyse et à la déconstruction de ces dispositifs.
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; maternité; postmodernisme; premier cycle; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Theorizing Homophobia - Adam, Barry D. (Sexualities, 1998)
A series of contemporary theories that have been used to explain homophobia are assessed. Structural, feminist, comparative, gender panic, queer, and socio-historical theories rely on the premises of a diverse set of scholarly disciplines, and in turn, generate their own objects of analysis, whether `homophobia', `heterosexism', or `heteronormativity'. While the current flourishing of gay and lesbian studies has generated important insights into the workings of homophobia, analyses have also tended to be limited and fragmentary. This paper suggests a study of homophobic projects that combines theoretical tools able to recognize experience, discourse, structure, and history.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Collection Les Entêtées, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

La conquête d'un espace public : les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; his4860; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; montréal; premier cycle; québec; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (Des hommes et des femmes en changement, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Les limites de l'identité sexuelle - Lamoureux, Diane (Itinéraires féministes, 1998)
Les études de Michel Foucault sur la sexualité et son histoire, de même que les premiers travaux de Judith Butler sur la fluidité des postures de genre, ont contribué à l’émergence de la pensée queer, qui récuse le fixisme identitaire sans pour autant rejeter la notion d’identité. Ce courant de pensée a eu des répercussions tant dans le domaine des études féministes que dans celui des études LGBT ou encore des études sur les sexualités qui s’intéressent aux marges de la société hétérosexiste. Au-delà des oppositions binaires du masculin et du féminin ou de l’hétérosexualité et de l’homosexualité, il y a toujours un indécidable, qui résiste à la bipartition, une zone de flou, d’hybride et de poreux. C’est cet indécidable qui force la réflexion, non pas pour le faire entrer dans une catégorie d’opposition binaire, mais pour faire rebondir la pensée. Des textes de Carmen Gill, Ross Higgins, Diane Lamoureux, Marie-José Nadal, Tania Navarro Swain, Paul-André Perron, Robert Schwartzwald et Colette St-Hilaire.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; europe; fem1000; france; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques

Only the Literal: The Contradictions of Anti-pornography Feminism - Segal, Lynne (Sexualities, 1998)
Within feminism, battles over pornography have become the wars without end. Despite the controversy it generates, the discourses of anti-pornography feminism have continued to make inroads into legal frameworks, most recently in Canada. This piece surveys the growth and questionable appeal of such feminist campaigning, under the theoretical leadership of Catharine MacKinnon: its rewriting of feminist theory; its parasitic relation to the authoritative, phallocentric discourses of gender and sexuality; its alliance with the most reductive, behaviouristic psychology; its disavowel of fantasy and psychic life; its provocative mirroring of both the style and content of the `pornography' it deplores; its unwavering pursuit of legal remedies which enhance the power of state regulation of sexuality; its threat to subversive expressions of women's sexual agency and repudiation of any possibilities for sexual resignifications.
Keywords: cours; discipline; droits des femmes*; histoire et politique; militance; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."--BOOK JACKET.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

Histoire comparee de l'homosexualite en Allemagne, en Angleterre et en France dans I'entre-deux guerres - Tarnagne, F. (ACTES DE LA RECHERCHE EN SCIENCES SOCIALES, 1998)
Keywords: 1900-1999; allemagne; angleterre; cours; discipline; entre-deux guerres; europe; france; his4860; histoire; histoire et politique; homosexualité; premier cycle; première guerre mondiale; royaume-uni; régions géographiques; sciences humaines; seconde guerre mondiale; sexualité; sexualités dissidentes; thématiques

Présentation : du fléau social au fait social. L’étude des homosexualités - Chamberland, Line (Sociologie et sociétés, 1997)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; homosexualité; identités LGBTQIA2+; militance; premier cycle; périodes historiques; sciences humaines; sciences sociales; sex1183; sexualité; soc2014; sociologie; thématiques

A feminist defense of pornography - McElroy, Wendy (Free Inquiry, 1997)
Keywords: approches et analyses; cours; intersectionnalité; point de vue situé; pornographie; premier cycle; ressource en ligne; sex1911; sexualité; thématiques

Des mots, des pratiques et des risques : la gestion différenciée de la parole et de la prévention du VIH chez des hommes à comportements bisexuels en France - Mendès-Leite, Rommel; Deschamps, Catherine (Sociologie et sociétés, 1997)
Cet article présente une partie des résultats de deux recherches socio-anthropologiques réalisées en France auprès d'hommes ayant des rapports sexuels avec des hommes et des femmes, indépendamment de leur identité socio-sexuelle. Les analyses portent d'abord sur les perceptions différenciées de la sexualité et sur ses conséquences en matière de restitution du sens, et ensuite sur la gestion des comportements préventifs. Ainsi il apparat!, au travers d'une relecture des notions de " multipartenariat ", de " sexe occasionnel " ou de " fidélité ", que le principal lieu de rupture dans la gestion des risques vin est avant tout dépendant de la variable sexe des partenaires sexuels, quand bien même la compréhension de ce mécanisme ne se réduit pas à une opposition basique entre hommes et femmes.
Keywords: 1900-1999; VIH; analyse différenciée selon les sexes -ADS+; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire et politique; hétérosexisme; justice sociale; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualité masculine; sociologie; systèmes d'oppressions; thématiques

Les usages de la sexualité chez Foucault - PROBYN, Elspeth (Sociologie et sociétés, 1997)
Cet article expose de façon schématique comment certains aspects de la pensée de Foucault dépassent les deux pôles qui ont défini la plupart des débats dans le champ des études gaies et lesbiennes à propos de la sexualité
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Le Red light de Montréal - Proulx, Daniel (Études québécoises, 1997)
"La légende du défunt quartier montréalais dit du "Red Light" vaut bien celle des Soho et Pigalle de ce monde. Prospères au début du siècle, les salles de jeux enfumées et les chambres sordides de nos bas-fonds deviennent dans les années trente les derniers refuges des damnés de la crise. La guerre venue, les entrepreneurs en plaisirs défendus font des affaires d'or, en attendant que l'armée s'en mêle. La guerre finie, le Red Light renaît en force. C'est alors que Pacifique Plante et Jean Drapeau entrent en scène et procèdent à l'épuration radicale de nos moeurs. Le rideau tombe sur notre quartier "réservé". Aujourd'hui, la "Main" n'est plus qu'un coin de rue, à l'intersection de Sainte-Catherine et de Saint-Laurent. Ni ses habitués ni les passants n'ont idée de son spectaculaire passé." -- Quatrième de couverture
Keywords: 1900-1999; amériques; canada; cours; discipline; his4860; histoire; histoire de la sexualité; histoire et politique; industrie du sexe; montréal; premier cycle; périodes historiques; québec; red light; régions géographiques; révolution tranquille; sciences humaines; sexualité; thématiques; travail; travail du sexe

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Fantasies of femininity: Reframing the boundaries of sex - Ussher, Jane M. (Rutgers University Press, 1997)
In Fantasies of Femininity, Jane Ussher focuses on unraveling the contradictory visions of feminine sexuality: the fact that representations of the definition of woman seethe with sexuality yet for centuries women have been condemned for exploring their own sexual desires. In her quest for the sources of feminine representation, Ussher interviewed dozens of women - as well as some men - and combed popular media - from Seventeen to Cosmopolitan and Dallas to Donahue - to identify what shapes women's symbolic images of sex and femininity. Ussher argues that women have effectively resisted and subverted these archetypal fantasies of femininity, and in the process of so doing, reframed the very boundaries of sex. In this way, she exposes as myth much of what we think we know about "woman" and about "sex."
Keywords: approches et analyses; cours; discipline; fem1000; inégalités; premier cycle; psychologie; sciences humaines; sexualité; sexualité féminine; stéréotypes; systèmes d'oppressions; thématiques; études culturelles

Queer studies: A lesbian, gay, bisexual & transgender anthology - Beemyn, Genny; Eliason, Michele J. (New York University Press, 1996)
This book is a wide-ranging anthology which discusses the nature and diversity of queer studies, its foundations, and some of the most pressing issues in the field.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identité sexuelle; identités; identités LGBTQIA2+; philosophie politique; postmodernisme; premier cycle; queer; sciences humaines; sex3383; sexualité; sociologie; thématiques

Quelle lesbienne êtes-vous? - Causse, Michèle (Parole de lesbiennes, 1996)
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétéronormativité; identités LGBTQIA2+; inégalités; lesbianisme; paris; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Mémoires lesbiennes : le lesbianisme à Montréal entre 1950 et 1972 - Chamberland, Line (De mémoire de femmes, 1996)
Line Chamberland retrace la vie de femmes qui ont eu le courage de leurs amours à une époque où la condamnation sociale du lesbianisme était unanime. À partir de nombreux témoignages, l’auteure démontre de quelle façon s’exerçait le contrôle social du lesbianisme, quel rôle jouait la famille et comment diverses instances comme les institutions religieuses, l’appareil judiciaire et les autorités psychomédicales veillaient à ce que ces femmes se conforment aux diktats, les poussant parfois à la marginalité ou les obligeant à adopter diverses stratégies de dissimulation.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; violences

Le Rose et le noir : les homosexuels en France depuis 1968 - Martel, Frédéric (Epreuve des faits, 1996)
"Ce livre est une chronique des homosexuels en France, hommes et femmes, depuis 1968. L’homosexualité est un fil rouge qui relie entre eux des phénomènes majeurs : libération sexuelle, féminisme, mutation des modes de vie, lutte contre le sida, pacs… Frédéric Martel évoque les figures emblématiques et les activistes, mais aussi les débats et les combats, tout ce qui a contribué à ce que les « gais » sortent de l’ombre. Plus visibles, mieux acceptés, les homosexuels sont aujourd’hui en quête de reconnaissance." -- Site de l'éditeur
Keywords: 1900-1999; LGBTQIA2+; activisme; approches et analyses; cours; discipline; discours militant; droits des femmes*; europe; france; his4860; histoire du féminisme; histoire et politique; homosexualité; hétérosexisme; identités LGBTQIA2+; justice sociale; lesbianisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Bisexualité: le dernier tabou - Mendès-Leite, Rommel; Deschamps, Catherine; Proth, Bruno-Marcel (Calmann-Lévy, 1996)
A partir de nombreux témoignages, ce livre dresse un portrait des bisexuels dans leur infinie variété, leur histoire, leur quotidien.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Mapping desire: geographies of sexualities - Bell, David; Valentine, Gill (Routledge, 1995)
This is the first book to explore sexualities from a geographical perspective. The nature of place and notions of space are of increasing centrality to cultural and social theory. Mapping Desire presents the rich and diverse world of contemporary sexuality, exploring how the heterosexual body has been appropriated and resisted on the individual, community and city scales. The geographies presented here range across Europe, America, Australasia, Africa, the Pacific and the imaginary, cutting across city and country and analysing the positions of gay men, lesbians, bisexuals and heterosexuals. The contributors ring different interests and approaches to bear on theoretical and empirical material from a wide range of sources. The book is divided into four sections: cartographies/identities; sexualised spaces: global/local; sexualised spaces: local/global; sites of resistance. Each section is separately introduced. Beyond the bibliography, an annotated guide to further reading is also provided to help the reader map their own way through the literature.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; géographie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

Les relations amoureuses entre les femmes du XVIe au XXe siècle. Essai historique. - Bonnet, Marie-Joe (Opus, 1995)
Voici la première histoire de l'amour entre les femmes qui, sur cinq siècles, de la Renaissance à nos jours, tienne compte à la fois du regard extérieur des hommes et de l'approche des lesbiennes elles-mêmes. Pour la première fois, aussi, une analyse à long terme est proposée qui dégage une évolution des moeurs, des mentalités et de la place des femmes dans la société. Jusqu'à présent, en effet, l'histoire des femmes occultait l'amour entre femmes, alors que les lesbiennes ont joué un rôle prépondérant dans les mouvements progressistes politiques et artistiques. Unique en son genre par son érudition, son approche pluridisciplinaire, ses mises en perspective originales et la période considérée, cet essai s'impose déjà comme un ouvrage de référence.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire des femmes*; histoire et politique; hétérosexisme; identités; identités LGBTQIA2+; invisibilités; lesbianisme; lit3220; premier cycle; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Fémininmasculin: le sexe de l'art. - Centre Georges Pompidou. (Passage du siècle, 1995)
Premier chapitre du Passage du siècle (les grands bilans que le Centre Georges Pompidou proposera en 1996 et 1997), cette exposition renoue avec des expériences décisives comme par exemple "Eros", organisée en 1959 par Marcel Duchamp et André Breton. A travers le titre "Féminin - Masculin, le sexe de l'art" s'exprime un double enjeu : celui de réhabiliter le terme dévalué d'une opposition inscrite dans la tradition des couples hiérarchiques de la pensée occidentale (forme/matière, vérité/mensonge, être/paraître, profondeur/surface, etc.) ; celui de montrer qu'au delà d'un simple sujet-motif artistique, le sexe est partie prenante des processus de l'art lui-même. L'ambition de cette exposition est de montrer, en dehors de toute approche chronologique, comment les productions artistiques du XXe siècle n'ont eu de cesse de venir brouiller les fatalités biologiques, anatomiques et culturelles traditionnellement liées au sexe. Aborder l'art dans la perspective de la différence sexuelle, ce n'est pas mécaniquement opposer un art "masculin" à un art "féminin", mais tenter de donner à voir comment les oeuvres se trouvent traversées par cette question, au-delà du sexe - du genre - des artistes qui les produisent. Féminin - Masculin, le sexe de l'art montrera aussi la coexistence dans ce siècle de deux généalogies artistiques concernant le sexe. L'une, à partir de Picasso, s'inscrit dans la tradition classique de la différence des sexes, conçue comme une opposition dialectique et organique du masculin et du féminin. L'autre, à partir de Marcel Duchamp, inaugure un nouveau type de relations, selon une logique asymétrique, faisant circuler les intensités masculines et féminines sur un mode proliférant qui opère une déterritorialisation des entités anatomiques, identificatoires et formelles. Les artistes de la jeune génération (tant américaine qu'européenne) semblent très sensibles à cette manière de déstabiliser les polarités traditionnelles du masculin et du féminin, mettant en oeuvre de nouvelles configurations éthiques et formelles qui se situent au-delà de la différence sexuelle, et en cela se distinguant en radicalement des positions identitaires des années 70.
Keywords: 1900-1999; LGBTQIA2+; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; exposition; har4600; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Sexy bodies: the strange carnalities of feminism - Grosz, E. A.; Probyn, Elspeth (Routledge, 1995)
Are bodies sexy? How? In what sorts of ways? Sexy Bodies investigates the production of sexual bodies and sexual practices, of sexualities which are dyke, bi, transracial, and even hetero. It celebrates lesbian and queer sexualities but also explores what runs underneath and within all sexualities, discovering what is fundamentally weird and strange about all bodies, all carnalities. Looking at a pleasurable variety of cultural forms and texts, the contributors consider the particular charms of girls and horses, from National Velvet to Marnie; discuss figures of the lesbian body from vampires to tribades to tomboys; uncover 'virtual' lesbians in the fiction of Jeanette Winterson; track desire in the music of legendary Blues singers; and investigate the ever-scrutinised and celebrated body of Elizabeth Taylor. The collection includes two important pieces of fiction by Mary Fallon and Nicole Brossard. Sexy Bodies makes new connections between and amongst bodies, cruising the borders of the obscene, the pleasurable, the desirable and the hitherto unspoken rethinking sexuality anew as deeply and strangely sexy.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; féminisme pop; identités LGBTQIA2+; lesbianisme; lit4700; premier cycle; queer; ressource en ligne; sexualité; thématiques

XXX: a woman's right to pornography - McElroy, Wendy (St. Martin's Press, 1995)
An unconventional argument for the preservation of pornography asserts that pornography can serve to benefit the feminist movement and promote sexual freedom for women, and explores the historical relationship between women and pornography.
Keywords: corps; cours; droits des femmes*; pornographie; premier cycle; sex1911; sexualité; thématiques

Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Sodomites, invertis, homosexuels: perspectives historiques - Mendès-Leite, Rommel (Cahiers Gai-Kitsch-Camp; no. 27; 5, 1994)
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

The Politics of Inside/Out: Queer Theory, Poststructuralism, and a Sociological Approach to Sexuality - Namaste, Ki (Sociological Theory, 1994)
This paper outlines the main tenets of poststructuralism and considers how they are applied by practitioners of queer theory. Drawing on both Michel Foucault and Jacques Derrida, queer theory explores the ways in which homosexual subjectivity is at once produced and excluded within culture, both inside and outside its borders. This approach is contrasted with more sociological studies of sexuality (labeling theory, social constructionism). Whereas queer theory investigates the relations between heterosexuality and homosexuality, sociologists tend to examine homosexual identities and communities, paradoxically ignoring the social construction of heterosexuality. Poststructuralism can inform a sociological approach to sexuality by emphasizing the generative character of all sexual identities. A sociological study of sexuality which is informed by poststructuralism would examine the exclusions implicit in a heterosexual/homosexual opposition. In this process, bisexual and transgender identities can become viable cultural possibilities, and a broad-based political coalition established. Whereas mainstream sociology focuses on the ways in which homosexuals are outside social norms, and whereas queer theory exploits the ways in which this outside is already inside, this perspective suggests that a critical sexual politics seeks to move beyond an inside/outside model.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; post-structuralisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; thématiques

Les constructions sociales de la sexualite - Bozon, Michel; Leridon, Henri (Population (French Edition), 1993)
Keywords: 1900-1999; approches et analyses; cours; discipline; premier cycle; production des savoirs; périodes historiques; rapports sociaux de sexe; sciences humaines; sciences sociales; sex1183; sexologie; sexualité; thématiques; épistémologie

Love and Intimacy: The Gender Division of Emotion and 'Emotion Work': A Neglected Aspect of Sociological Discussion of Heterosexual Relationships - Duncombe, Jean; Marsden, Dennis (Sociology, 1993)
This paper discusses the role of ideologies of love and intimacy in heterosexual coupledom, and examines the applicability of theories of the gender division of 'emotion work' to the field of intimate personal relationships. Research on the private sphere of the family has recently focused on quantifying instrumental aspects of relationships, such as financial management, the domestic division of labour and informal care. However, although fruitful, such approaches neglect the expressive or emotional; particularly the experiences of love and intimacy, which many people say they regard as a key element in their personal relationships. We suggest reasons for British sociology's neglect of what is almost a cliche in everyday discourse. And we present evidence (including preliminary findings from our own research on heterosexual couples) that - despite dissatisfaction with gender inequalities in domestic tasks and finance - many women express unhappiness primarily with what they perceive as men's unwillingness or incapacity to `do' the emotional intimacy which appears to them necessary to sustain close heterosexual couple relationships. We illustrate how similar discussions of gender differences in emotional behaviour have emerged elsewhere (including in the new masculinity literature), raising questions about how far men's and women's emotional behaviour can and should change.; The exploration of socially-regulated or `managed' gender divisions in intimate emotional behaviour entails two related but distinct questions: are men and women equally `susceptible' to the emotions or discourses of love and intimacy; and, do they handle such emotions in similar ways in the context of close personal relationships. We suggest how research findings on heterosexual couple relationships can be linked to work on the social regulation of emotion, which argues that there is a `gender division of emotion work' where it is assumed that women will take responsibility for the management of emotion in the private sphere.
Keywords: 1900-1999; 1980-1989; angleterre; approches et analyses; care; cours; discipline; emotional labor; europe; hétérosexualité; postmodernisme; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques; travail

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography--or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography--an act of sexual domination reproduced in the viewing--is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Wild desires & mistaken identities: lesbianism and psychoanalysis - O'Connor, Noreen; Ryan, Joanna (Between men--between women, 1993)
This groundbreaking book provides a challenging exploration of psychoanalytic ideas about lesbians and lesbianism. Based on the authors' clinical experience as psychoanalytic psychotherapists, it offers a new and thoughtful framework that does not inevitably pathologise or universalise all lesbianism. A wide range of psychoanalytic ideas are surveyed, from Freud, Deutsch and Jung to Lacan and contemporary object-relations theorists. Questions on sexual identity, sexual desire and gender identity, of transference and countertransference, and also of institutional practices in relation to training, are all critically - and stimunlatingly - addressed.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; désir lesbien; lesbianisme; premier cycle; psychanalyse; sciences humaines; sexualité; soc2014; thématiques

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Un genre trouble: le féminisme, la pornographie, la réforme du droit et la thèse de la reproduction de l'ordre social - Lacombe, D. (Déviance et société, 1992)
L'étude de la campagne de criminalisation de la pornographie au Canada, dans les années 1980, pose un défi au savoir conventionnel qui s'est développé, en sociologie et en criminologie, sur la réforme du droit. Ce savoir est l'argumentation selon laquelle les réformes, en dispersant le contrôle social, ne font que légitimer le système sans le modifier fondamentalement. Afin d'éviter l'essentialisme de ce savoir, j'ai utilisé une approche reflexive qui pense la relation entre la réforme du droit et le pouvoir comme à la fois contraignante et facilitante. L'établissement d'un lien entre la pornographie et la déviance sociale n'apparaît pas comme une construction sociale unifiée, mais comme un terrain contesté dans lequel se produisent des rapports de pouvoir complexes, et une multiplicité de stratégies de résistance. C'est dans ce sens que la réforme apparaît comme un mécanisme générateur des pratiques.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; criminologie; discipline; droit; féminisme pop; justice sociale; pornographie; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; thématiques

La fabrique du sexe : essai sur le corps et le genre en Occident - Laqueur, Thomas Walter (NRF essais, 1992)
L'Occident n'a cessé depuis les origines de s'interroger sur la différence des sexes. Mais parle-t-on de l'homme et de la femme que l'on n'a encore rien dit : se réfère-t-on au genre - définition culturelle par des qualités morales, affectives, sociales... - ou au sexe - définition par des spécificités anatomiques ? Jamais, en effet, les deux notions ne se recouvrirent, rappelle Thomas Laqueur dans cet ouvrage qui demeure une référence majeure. Dès l'Antiquité, Aristote, par la définition de l'ordre des êtres, et Galien, par la définition du corpus anatomique, fondent le modèle du sexe unique, qui sera dominant jusqu'au XVIIIe siècle, et dans lequel le genre définit le sexe. Au XVIIIe siècle émerge l'autre modèle de la différence sexuelle, le modèle des deux sexes, dans lequel, au contraire du premier, le sexe définit le genre : parce que, au niveau de l'anatomie comme de la physiologie, femmes et hommes sont incommensurablement différents, les genres définissent dès lors qualités, vertus et rôles selon des racines biologiques. Ces deux modèles coexistent dans le temps - dès le XVIe siècle des auteurs posent l'irréductible différence anatomique, alors qu'au XXe siècle encore Freud pense la sexualité selon le modèle du sexe unique - car leur prégnance sur les esprits, si elle est liée à des évolutions générales - économiques, culturelles, sociales -, ne peut en aucun cas être strictement expliquée par celles-ci; et moins encore par les progrès de la connaissance anatomique, qui se moulent le plus souvent dans les représentations dictées par chacun de ces modèles...
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; corps; cours; discipline; discours dominant; essentialisme; féminisme matérialiste; genre; histoire; histoire et politique; hétérosexisme; occident; philosophie politique; premier cycle; production des savoirs; périodes historiques; sciences humaines; sciences sociales; sex1183; sex3383; sexe/genre; sexualité; systèmes d'oppressions; thématiques; épistémologie

L'amant de la Chine du Nord - Duras, Marguerite (Collection Folio, 1991)
SommaireLe Chinois et l'adolescente. Le dernier avatar des amours indochinoises d'une auteur douée pour les tragédies familiales. Roman inspiré et provoqué par le scénario et la mise en images d'un précédent roman de l'auteure, « L'amant »…»-- [SDM]
Keywords: arts; asie; cours; discipline; indochine; lit3220; littérature; premier cycle; roman; régions géographiques; sexualité; thématiques; vietnam; écriture des femmes*; études littéraires

From mastery to analysis: Theories of gender in psychoanalytic feminism - Elliot, Patricia (Cornell University Press, 1991)
Critique des approches psychanalytiques en études féministes et de l'hystérie (Kristeva, Irigaray, Chodorow, Dinnerstein, Mitchell, Lacan, Freud) Voir le compte-rendu: Williams, C. L. (1992). [Review of From Mastery to Analysis: Theories of Gender in Psychoanalytic Feminism., by P. Elliot]. Contemporary Sociology, 21(5), 728–729. https://doi.org/10.2307/2075599
Keywords: 1900-1999; corps; cours; discipline; europe; fem1000; france; maternité; premier cycle; psychanalyse; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sexualité; thématiques

In Dora's case: Freud, hysteria, feminism - Bernheimer, Charles; Kahane, Claire (Columbia University Press, 1990)
A collection of essays that question Freud's assumptions about femininity and female desire. Several essays situate their critiques within the context of contemporary French writing on psychoanalysis and feminism, while others display the variety and finesse of the interpretive strategies exercised by contemporary feminist critics.
Keywords: approches et analyses; cours; discipline; fem1000; inégalités; premier cycle; psychanalyse; santé; santé des femmes*; sciences; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Women, art, and society - Chadwick, Whitney (Thames and Hudson, 1990)
L'étude à succès acclamée de l'historienne de l'art Whitney Chadwick remet en question l'hypothèse selon laquelle les grandes femmes artistes sont des exceptions à la règle qui ont « transcendé » leur genre pour produire des œuvres d'art majeures. Tout en présentant certaines des nombreuses femmes depuis le Moyen Âge dont les contributions à la culture visuelle ont souvent été négligées, l'enquête de Chadwick réexamine les œuvres elles-mêmes et la manière dont elles ont été perçues comme marginales, souvent en référence directe au genre. Dans sa discussion sur le féminisme et son influence sur une telle réévaluation, elle aborde également les questions étroitement liées de l'ethnicité, de la classe et de la sexualité.
Keywords: LGBTQIA2+; amériques; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; régions géographiques; sexualité; thématiques; états-unis

Queer Nation Manifesto - Queer Nation (Infokiosk, 1990)
Texte d’un manifeste initialement distribué par des personnes marchant aux côtés du contingent d’Act Up à la Gay Pride de New York, 1990.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; act up; amériques; approches et analyses; cours; gay pride; manifeste; militance; new york; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; violences; états-unis